PENGARUH KEPEMIMPINAN KEPALA SEKOLAH TERHADAP DISIPLIN KERJA GURU DI SD NEGERI 060794 KECAMATAN MEDAN AREA - Muhammad rifa'i (Universitas Islam Negeri Sumatera Utara Medan, 2018)
Formulation of the problem in this research is how the State leadership of the headteacher at 060794 primary school Medan Area, how is the State of the discipline of Islamic education teachers working in primary school 060794 Medan Area, and whether There was significant influence between the leadership of headteacher work discipline against Islamic religious education teachers in elementary school 060794 Medan Area. As for the purpose of this research is to know the State of the leadership of the headteacher at 060794 primary school Medan Area, to know the State of the working discipline teacher of Islamic education in the elementary school 060794 Medan Area, and to knowing the significant influence among the leadership of headteacher work discipline against Islamic religious education teachers in elementary school 060794 Medan Area. The research method used is a quantitative method. Research instrument used IE now and observations. The results of the analysis show that the teaching skills of elementary school teachers in 060794 subdistrict Medan Area is quite good, it is characterized by the presence of the teacher's efforts to improve the quality of learning for students, carry out the Indeed so that the learning objectives can be achieved. Based on the results of the study showed that there was significant influence between the leadership of headteacher work discipline against Islamic religious education teachers, this is evidenced based on the calculation that the values obtained rxy = 0.50 with the category is or.Keywords: Principal Leadership, discipline, Teacher of Islamic Education